Studies of seabirds at Svarthamaren - Tveraa, Torkild; Andreassen, Cecilie; Christensen, Guttorm N (Report of the Norwegian Antarctic Research Expedition 1997/98, 1999)
Keywords: Dronning Maud Land; NARE 1997/98; fugler; ornitologi; petreller

Effects of Egg Size and Parental Quality on Early Nestling Growth: An Experiment with the Antarctic Petrel - Amundsen, Trond; Lorentsen, Svein-Hakon; Tveraa, Torkild (Journal of Animal Ecology, 1996)
A large number of studies have reported a positive relationship between the egg size of birds and the subsequent growth and/or survival of nestlings, but such effects may partly be due to confounding variables, e.g. parental quality. In order to evaluate the potential effects of egg size, and of parental quality, on early nestling growth in the Antarctic petrel, we performed an experiment in which eggs of different size were swapped between nests. 2. From a sample of 300 nests with eggs of known size, we selected eggs belonging to the lower quartile (small eggs), and those belonging to the upper quartile (large eggs), with respect to volume. Half of the small eggs were exchanged with small eggs from other nests, and the other half with large eggs. A similar procedure was used for large eggs. Growth and survival of the nestlings were recorded until 12 days old. 3. Hatching success was positively related to egg size. 4. Egg size influenced nestling body mass until the age of 3 days, and tarsus length was affected until 12 days old. However, these effects were not due to an effect of egg size on growth rates, but reflected instead the influence of egg size on hatchling size. 5. In contrast to most previous studies, we found no effect of parental quality (as reflected in the size of own eggs) on foster nestling size or growth until 12 days old. This could be because egg size does not reliably reflect parental quality in the species, or because parental effects become evident only at later nestling stages. 6. We discuss why egg size variation is maintained in this and other species where egg size influences parental fitness through the survival of eggs or nestlings.
Keywords: Dronning Maud Land; fugler; ornitologi; petreller; zoologi; økologi

Regulation of foraging trips and costs of incubation shifts in the Antarctic petrel (Thalassoica antarctica) - Tveraa, Torkild; Lorensten, Svein-Håkon; Sæther, Bernt-Erik (Behavioral Ecology, 1997)
In species where incubation is shared by both parents, the mate's ability to fast on the nest may constrain the time available for foraging. The decision to return to the nest should therefore be a compromise between an animal's own foraging success and its mate's ability to fast on the nest. To examine how the body conditions of incubating Antarctic petrels, Thalassoica antarctica, influence both the length of foraging trips and incubation shifts, we experimentally handicapped females by increasing their flight costs during a foraging trip by adding lead weights to their legs. Handicapped females spent more time at sea and had lower body conditions at arrival to the colony than controls, and, moreover, females in poor body condition at arrival to the colony spent generally more time at sea than those with higher body condition. The prolonged time period spent at sea by handicapped females was associated with higher desertion rates than among controls. The time the incubating mates fasted increased with their body condition at arrival to the colony, suggesting that a high body condition of the incubating bird may reduce the probability of nest desertion. Accordingly, our results suggest that the time spent foraging is adjusted to the body conditions of both the foraging and incubating mate.
Keywords: Dronning Maud Land; fugler; ornitologi; petreller; zoologi; økologi

Seabird research at Svarthamaren during NARE 1993/94 - Lorentsen, Svein-Håkon; Amundsen, Trond; Røv, Nils; Tveraa, Torkild (Report of the Norwegian Antarctic Research Expedition 1993/94, 1996)
Keywords: Dronning Maud Land; NARE 1993/94; fugler; ornitologi

Regulation of food provisioning in the Antarctic petrel; the importance of parental body condition and chick body mass - Tveraa, Torkild; Sether, Bernt-Erik; Aanes, Ronny; Erikstad, Kjell Einar (Journal of Animal Ecology, 1998)
1. Two hypotheses may explain how long-lived seabirds regulate the food provisioning to their chick. The fixed level of investment hypothesis states that the parents provide food for their chick according to an intrinsic rhythm, independent of their chick's need. The flexible investment hypothesis states that the parents adjust their food provisioning both according to their chick's and their own need. 2. We tested how the Antarctic petrels adjust the food-provisioning according to their own body condition or to their chick's need. First, we selected parents in poor and good body condition. Then we gave all parents randomly a chick of different body mass, but of the same age. We then measured the chicks daily until they were fed for the first time after swapping. 3. Parents in good body condition at hatching were more likely to produce a chick that was still alive 9 days after hatching than parents in poor body condition. Chick body mass at day 9 and at the end of the guarding period was positively related to the mean body condition of the parents at hatching. 4. The meal size provided by parents in good body condition was larger than that provided by parents in poor body condition. Parents in good body condition delivered more food to small than to large chicks, whereas no such relationship was found among parents in poor body condition. 5. Our results suggest that the Antarctic petrel parents adjust the amount of food delivered to their chick according to both the chick's need and their own body condition, and that the ability to respond to the chick's need is dependent upon their own body condition.
Keywords: Dronning Maud Land; NARE 1996/97; fugler; ornitologi; petreller; zoologi

Body mass and parental decisions in the Antarctic petrel Thalassoica antarctica : how long should the parents guard the chick? - Tveraa, Torkild; Sæther, Bernt-Erik; Aanes, Ronny; Erikstad, Kjell Einar (Behavioral Ecology and Sociobiology, 1998)
In Procellariiformes, the parents guard the chick after it has attained homeothermy. This strategy may reduce the probability that a small chick is taken by predators, but is costly as only one parent can forage at a time. The decision to leave the chick may therefore be a compromise between the chick's vulnerability to predators, the body condition of the parent on the nest and whether the foraging parent returns in time. We studied how the number of days that parents guarded the chick was related to the body mass of the parent at the nest and the time the foraging parent spent at sea in the Antarctic petrel Thalassoica antarctica. We also examined how the body mass of the parent on the nest and the duration of the foraging trips influenced the chicks' body condition at the end of the guarding period. When the foraging parent did not return to the nest in time to relieve its mate, the number of days the parent on the nest kept guarding the chick was positively related to its body mass on arrival in the colony. The number of days the foraging parent spent at sea was positively related to the body mass of its mate, but those that returned in time had a shorter stay at sea relative to their mate's body mass than those that did not return before their mate had left. Apparently, both the body mass of the parent at the nest and the ability of the foraging parent to adjust its stay at sea to the mate's body mass is important for the number of days the parents guard the chick and also the chick's body condition at this point. The inability to return to the nest before the mate has left may be the result of needing a minimum amount of time at sea to find food, or because some parents having low foraging success and therefore prolong their stay at sea.
Keywords: Dronning Maud Land; NARE 1996/97; fugler; ornitologi; petreller; zoologi

Seabird research at Svarthamaren during NARE 1996-1997 - Tveraa, Torkild; Røv, Nils; Aanes, Ronny; Jensen, Henrik (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: Dronning Maud Land; NARE 1996/97; fugler; ornitologi; petreller

Size-Dependent Variation in Reproductive Success of a Long-Lived Seabird, the Antarctic Petrel (Thalassoica Antarctica) - Sæther, Bernt-Erik; Lorentsen, Svein-Håkon; Tveraa, Torkild; Andersen, Reidar; Pedersen, Hans Christian (The Auk, 1997)
We examined how variation in parental quality influences the reproductive success of a long-lived seabird, the Antarctic Petrel (Thalassoica antarctica). In particular, we focused on how quality of parents can interact with and influence the effects of stochastic variation in the environment due to varying climatic conditions. Large annual variation was found in reproductive success. However, body mass of individual chicks at the end and be ginning of the nestling period was strongly correlated in two of the study years, suggesting consistent variation among parents in their ability to feed offspring. Furthermore, chick mass was related both to overall body size and to body mass of their parents. Short brooding-shift intervals also were important for growth and survival of chicks. The probability of chick survival to the age of 30 days (ca. two weeks before fledging) was strongly correlated with chick mass when the chick was left unattended. However, the relative importance of different parental characteristics differed between years. These results show that reproductive success of the Antarctic Petrel is influenced by stochastic variation in the environment, probably re lated to climatic conditions. Effects of this stochastic variation may depend on body mass and/ or body condition of the parents.
Keywords: Dronning Maud Land; NARE 1989/90; NARE 1991/92; NARE 1992/93; fugler; ornitologi; petreller; zoologi

EPICA Dronning Maud Land pre-site survey - Karlöf, Lars; Gjerde, Knut; Winther, Jan-Gunnar (Report of the Norwegian Antarctic Research Expedition 1997/98, 1999)
Keywords: Dronning Maud Land; NARE 1997/98; geodesi; innlandsis; topografi